A real‐time WAXS and SAXS study of the structural evolution of LLDPE bubble. Issue 20 (10th October 2018) - Zhao, Haoyuan; Zhang, Qianlei; Ali, Samard; Li, Lifu; Lv, Fei; Ji, Youxin; Su, Fengmei; Meng, Lingpu; Li, Liangbin
ABSTRACT: The structural evolution during the linear low‐density polyethylene (LLDPE) film blowing has been studied with a combination of home‐made blown film apparatus and in situ WAXS and SAXS measurements. Analyzing the evolution of orientation parameters and crystallinity of the bubble shows that the blown film process can be divided into four regions. Distinctly different features of LLDPE bubble are observed in first three regions: (a) lower orientation parameters during the blown film process, (b) higher crystallinity is required to form a deformable crystalline crosslinked network, and (c) the weaker stretching effect and the difficulty of reaching equilibrium when the crystal network deforms. These results should provide a basis for understanding the poor blown film stability of LLDPE. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1404–1412 Abstract : In situ WAXS and SAXS technique studies have been used successfully to investigate the structural evolution during the linear low‐density polyethylene (LLDPE) film blowing. It is found that the LLDPE blown film process can be divided into four regions. The higher crystallinity in the end of Region II and the weaker change of orientation in Region III are expected to explain the LLDPE blown film poor stability.